From heart for heart: a conversation between friends - de Siqueira, José Eduardo (O Mundo da Saúde, 2007)
The importance of keeping the heart healthful is easily perceived when some data on the performance of this wonderful bomb are observed. One needs only know that the heart of a normal adult contracts from 60 to 80 times a minute when in rest and from 120 to 180 when in physical exercises, or in situations of emotional tension. Thus, the number of beatings in one day surpasses 100.000. From 6.500 to 7.000 liters of blood pass in one day through the heart. At the end of the life of a person in age 80, about three hundred million liters will circulate through the heart. Not bad for an organ that is composed by two bombs that press and inspire and are endowed with ingenious automatic electric coordination that almost simultaneously keeps filling and ejection of the two ventricles. The functional integrity of the heart is essential for the perfect health of the human body. Organs and tissues have their vitality preserved by the adequate supply of blood stimulated by the heart. Thus it is easy to understand that any restriction on its performance will impose unfavorable consequences to the organism. The cares to be taken for keeping it healthful are the reason of this article.